2018
DOI: 10.1021/acs.cgd.8b00331
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Infinite Number of Components in a Single Crystalline Phase: On the Isomorphism of Brivaracetam–Guest Molecules

Abstract: This article highlights the unusual behavior of brivaracetam (BRV: an active pharmaceutical ingredient against epilepsy), which leads to a unique phaseranging from clathrate to solvate to cocrystalformed with an impressive number of apolar guest molecules (any linear alkanes to esters of fatty acids/alcohols, or waxes). Moreover, the investigation of binary systems between linear alkanes and BRV displayed the systematic existence of a syntectic invariant (one solid melts into two nonmiscible liquids) for C n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…It may appear as rectangular rods, called Phase I crystals, and as needle-shaped crystals, designated as Phase II crystals. 22 The solubilities of both crystalline forms are very close to each other, as shown in Figure 3. It was found that both forms can coexist in a temperature range between 15 and 25 °C as shown in the inset of Figure 3.…”
Section: ■ Results and Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It may appear as rectangular rods, called Phase I crystals, and as needle-shaped crystals, designated as Phase II crystals. 22 The solubilities of both crystalline forms are very close to each other, as shown in Figure 3. It was found that both forms can coexist in a temperature range between 15 and 25 °C as shown in the inset of Figure 3.…”
Section: ■ Results and Discussionsupporting
confidence: 53%
“…Brivaracetam crystallizes into two different crystal forms. It may appear as rectangular rods, called Phase I crystals, and as needle-shaped crystals, designated as Phase II crystals . The solubilities of both crystalline forms are very close to each other, as shown in Figure .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…These appear as rectangular rods called Phase I crystalsthe thermodynamically stable solid form at ambient temperatureand as needle-shaped crystals, designated as Phase II crystals, a pseudo-polymorph. 29 Consequently, Phase I crystals are the desired crystalline form for production. As described in Part 1 companion paper, the solubility curves of both crystalline forms are close to each other, and both phases coexist between 15 and 25 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27,28 Brivaracetam crystallizes in two distinct forms: rectangular rods (Phase I) as the desired form for drug uptake and processability and needle-shaped crystals (Phase II). 29 A companion paper in this issue (Part 1, DOI: 10.1021/acs.cgd.8b00928) describes the development of a selective protocol to crystallize the desired crystalline form of Brivaracetam through cooling crystallization with the aid of a tubular crystallizer. This part describes the challenge to design a protocol to continuously crystallize the API in the desired crystalline form using a combination of cooling and antisolvent crystallization directly mixed using microfluidic connectors.…”
Section: ■ Introductionmentioning
confidence: 99%